New US export controls: Key policy choices for Europe. Recommendations for a robust European export control policy - Martin Chorzempa; Laura von Daniels (Stiftung Wissenschaft und Politik (SWP), 2023)
In response to Russia's attack on Ukraine, the United States and 37 countries formed a coalition in February 2022 to implement a barrage of export controls outside of any formal arrangement. By contrast, US controls on China are often unilateral, such as its October 2022 measures on semiconductors that went ahead without explicit consent, let alone a commitment by its allies to join. But to deny China access to 'dual-use' technology, unilateral export controls will not be effective. As European Commission President Ursula von der Leyen announced during her visit to the White House, the European Union (EU) wants to renew its export controls on dual-use products and new technologies and to coordinate them more closely with US measures. That means that member states will need to develop a common position on the scope of their export controls - including the extent of their alignment with the United States - as well as ways forward with multilateral controls of dual-use goods, given the freeze of the Wassenaar Arrangement due to Russia's actions.
Keywords: 320; Russia's attack on Ukraine; China; Huawei; export controls; European Commission; "dual-use" technology; Wassenaar Arrangement